CuTiPS5 – A New Structure Type with a Corrugated Layered Network Structure. Issue 23 (21st July 2017) - Dressel, Carina B.; Klein, Wilhelm; Fässler, Thomas F.
Abstract : The reaction of the binary sulfides TiS2 and P4 S10 with the elements Cu and S for 10 h at 750 °C and subsequent annealing at 550 °C for 21 d result in the novel compound CuTiPS5, which crystallizes in the triclinic space group P 1 with a = 6.8381(12), b = 6.9905(12), c = 14.612(3) Å, α = 90.057(6)°, β = 101.771(7)°, γ = 103.165(7)°, Z = 4, R 1 = 1.87 %, wR 2 = 4.74 % (all reflections) and represents the first quaternary copper titanium thiophosphate. The crystal structure contains 1 ∞ [Cu2 Ti2 (PS4 )2 S2 ] chains built from TiS6 octahedra and PS4 and CuS4 tetrahedra, which are connected by common edges and linked via common vertices to form layers. The anionic [TiPS5 ] – partial structure has been found previously, whereas the distinct 2D extension of the network is observed for the first time in compounds with such a M TiPS5 composition. The structure resembles sections of the TiS2 and Cu3 PS4 structures, which were found in the reaction as by‐products. Abstract :